THE RELATIONSHIP BETWEEN PRE-CLINICAL STUDENT LEARNING MOTIVATION AND CLINICAL STUDENT WITH ACADEMIC PERFORMANCE DURING THE DISTANCE LEARNING PERIOD AT THE FACULTY OF MEDICINE, UM SURABAYA - Hendy Marseta Putra; Muhammad Reza Utama; Yelvi Levani (Universitas Muhammadiyah Surabaya, 2023)
The COVID-19 pandemic that lasts for a long time will make students' learning motivation varied and can affect academic achievement. To find out the relationship between learning motivation and academic achievement of students of the Faculty of Medicine, University of Muhammadiyah Surabaya during the covid-19 pandemic. The study used an analytical observational method with a cross sectional approach. Data was collected by asking for permission and ethical approval, preparing instruments that have been tested for validity and reliability, distributing questionnaires that meet the inclusion criteria, submitting informed consent, then asking for permission to collect IP semester data in the academic section.Keywords : Academic Motivation Scale, Academic Performance, Distance Learning, Covid-19Â Pandemic.